2021
DOI: 10.1021/acs.joc.0c02777
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Carbonyl Trisubstituted Furans via Pd-Catalyzed Aerobic Cycloisomerization Reaction: Development and Mechanistic Studies

Abstract: Herein, we report the synthesis of 3-carbonyl-trisubstituted furans via Pd-catalyzed oxidative cycloisomerization reactions of 2-alkenyl-1,3-dicarbonyl scaffolds, using molecular oxygen as the sole oxidant to regenerate active palladium catalytic species, featuring good functional tolerance and mild reaction conditions. Deep investigation of intermediates and transition states of the reaction mechanism were conducted via experimental and DFT studies, providing a detailed mechanistical profile. The new develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Hashmi and Ma et al independently reported the Pd-catalyzed dimerization of allenyl ketones to afford di- and trisubstituted furans (Scheme b,c). , Additionally, the Widenhoefer group demonstrated the synthesis of 2,3,5-trisubstituted furans from oxidative alkoxylation of α-alkenyl β-diketones by using PdCl 2 (CH 3 CN) 2 (Scheme d) . Recently, a very similar kind of synthesis of 3-carbonyl trisubstituted furans via a palladium-catalyzed oxidative cycloisomerization reaction of the 2-alkenyl-1,3-dicarbonyl moiety was reported by the Ferreira group …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hashmi and Ma et al independently reported the Pd-catalyzed dimerization of allenyl ketones to afford di- and trisubstituted furans (Scheme b,c). , Additionally, the Widenhoefer group demonstrated the synthesis of 2,3,5-trisubstituted furans from oxidative alkoxylation of α-alkenyl β-diketones by using PdCl 2 (CH 3 CN) 2 (Scheme d) . Recently, a very similar kind of synthesis of 3-carbonyl trisubstituted furans via a palladium-catalyzed oxidative cycloisomerization reaction of the 2-alkenyl-1,3-dicarbonyl moiety was reported by the Ferreira group …”
Section: Introductionmentioning
confidence: 87%
“…18 Recently, a very similar kind of synthesis of 3-carbonyl trisubstituted furans via a palladium-catalyzed oxidative cycloisomerization reaction of the 2-alkenyl-1,3-dicarbonyl moiety was reported by the Ferreira group. 19 It is also worth mentioning that the intramolecular acetalization of a dihydroxy-substituted geminal alkene to provide fused perhydrofurans under Wacker-type conditions was reported by Alonso et al 20 Even, the group of Runeberg 21 and Gracza 22 disclosed the remarkable synthesis of oxaheterocyclic core intermediates differently via Pd-catalyzed Tsuji− Wacker type cyclization, where they unexpectedly got disubstituted furan as a byproduct. Rao et al used I 2 and DBU to cyclize the diols with an olefin in the middle of their reaction sequence.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Recently, our group reported a significant contribution towards the aerobic Wacker-type cycloisomerization protocol for the synthesis of 3-carbonyl trisubstituted furans by using 2-alkenyl-1,3-dicarbonyl scaffolds, an underexplored substrate in this approach, and avoiding the use of stoichiometric amounts of oxidants and strong acid additives (Scheme 5). 20 These mild conditions demonstrated good functional group tolerance and afforded good to excellent yields. In addition, a detailed study of the mechanism was carried out through DFT calculations and by kinetic and multivariate linear regression (MLR) analysis.…”
Section: Scheme 4 An Aerobic Approach To Aminopalladation and Sequential Proxicyclic Dehydropalladationmentioning
confidence: 94%
“…Interested in metal‐catalyzed aerobic oxidative processes, [53] Ferreira et al. in 2021 explored the synthesis of 3‐carbonyl‐trisubstituted furans 45 via Pd‐catalyzed Wacker‐type cycloisomerization of 2‐alkenyl‐1,3‐dicarbonyl scaffolds 44 using O 2 as the sole oxidant under mild reaction conditions in good to moderate yields [54] . The mechanistic investigations are supported by DFT calculations, NMR experiments, multivariate regression analysis and KIE experiments.…”
Section: Transition‐metal Catalyzed Synthesismentioning
confidence: 99%